2017
DOI: 10.1016/j.dsr2.2017.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Controls on turbulent mixing on the West Antarctic Peninsula shelf

Abstract: The ocean-to-atmosphere heat budget of the West Antarctic Peninsula is controlled in part by the upward flux of heat from the warm Circumpolar Deep Water (CDW) layer that resides below ~200 m to the Antarctic Surface Water (AASW), a water mass which varies strongly on a seasonal basis. Upwelling and mixing of CDW influence the formation of sea ice in the region and affect biological productivity and functioning of the ecosystem through their delivery of nutrients. In this study, 2.5-year time series of both Ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
30
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 48 publications
6
30
1
Order By: Relevance
“…A recent observational study made significant progress in understanding the sources and temporal variability of mixing on the shelf [ 73 ]. Using a 2.5 year-long time series of ocean velocity profiles, hydrographic profiles and wind velocity from Ryder Bay ( figure 1 ), wind-driven currents are shown to be a key source for mixing, with the time variability and intensity of this process being heavily modulated by the timing of ice retreat.…”
Section: Budgets Of Heat and Salt On The West Antarctic Peninsula Shementioning
confidence: 99%
“…A recent observational study made significant progress in understanding the sources and temporal variability of mixing on the shelf [ 73 ]. Using a 2.5 year-long time series of ocean velocity profiles, hydrographic profiles and wind velocity from Ryder Bay ( figure 1 ), wind-driven currents are shown to be a key source for mixing, with the time variability and intensity of this process being heavily modulated by the timing of ice retreat.…”
Section: Budgets Of Heat and Salt On The West Antarctic Peninsula Shementioning
confidence: 99%
“…Nevertheless, some of the regional flows and physical processes that impact the water mass mixing, hydrography, and the advection of surface, intermediate and shelf waters in the region are still undetermined. For example, new information is needed for a better understanding of (i) intrusions of Warm Deep Water (a Weddell Sea local water mass sourced by CDW) at intermediate levels from the Powell Basin toward the Bransfield Strait (e.g., Azaneu et al, 2017); (ii) the periodicity and frequency of CDW intrusions along the western continental shelf of the NAP (e.g., Moffat et al, 2009;Couto et al, 2017;McKee et al, 2019); (iii) the rate of water masses mixing along the deep Bransfield basins (e.g., Brearley et al, 2017); and (iv) the rate of Weddell Sea shelf waters advection and renewal from the east (e.g., Renner et al, 2012;Dotto et al, 2016). All these unknown mechanisms directly impact the vertical stratification of the upper water column, consequently, impacting the development and distribution of the phytoplankton groups due the local and regional changes of the physical and chemical properties.…”
Section: Ocean Circulation In the Napmentioning
confidence: 99%
“…Although ERA-Interim is seen as the most reliable reanalysis over this area (Bracegirdle, 2013), Rodrigo et al (2013) argue that spatial resolution in the ERA-Interim dataset is not high enough to capture synoptic high-wind events and observe that ERA-Interim underestimates wind speed in the ice shelf areas around Ross Ice Shelf. Lower wind speed could also lead to shallower MLD in the model results, as Brearley et al (2017) have found that direct impact of storms on ocean surface is responsible for a large portion of the surface ocean mixing in the WAP shelf.…”
Section: Discussionmentioning
confidence: 86%
“…The biases towards shallower MLD could also be related to other limitations in the model configuration. A higher horizontal resolution could improve the model by better resolving eddy activity and coastal circulation; and adding tides could also have an impact in the vertical mixing, although Brearley et al (2017) find that tidally driven mixing is weak in the WAP shelf. Although ERA-Interim is seen as the most reliable reanalysis over this area (Bracegirdle, 2013), Rodrigo et al (2013) argue that spatial resolution in the ERA-Interim dataset is not high enough to capture synoptic high-wind events and observe that ERA-Interim underestimates wind speed in the ice shelf areas around Ross Ice Shelf.…”
Section: Discussionmentioning
confidence: 99%